Algunos aspectos da utilizacao de imagens de radar e la satelite no estudo da superficie do terreno. - Garcia, G. J. (My University, 1984)
The drainage network of an area situated in the State of Sao Paulo was delineated through aerial photographs, radar and satellites images respectively and three base maps were prepared. On these three basic maps the length and number of streams were analysed using the following indices: drainage density, frequency of streams and average length of steams. The relief and the scanning direction of the SLAR images were also considered. -English summary
(Some aspects of the use of radar and satellite images in the study of the terrain surface, Brazil).